Autocratic Challenges to International Human Rights Law: A Chinese Case Study - Pils, Eva (Current Legal Problems, 2022)
Drawing on a case study of the implications of China's atrocities in Xinjiang in the context of China's historical engagement with UN and its human rights mechanisms, this article examines autocracies' impact on the institutions and practices of international human rights law. It argues that that rather than creating new law that turns international law as a whole (more) authoritarian, the Chinese party-state is primarily - and even more dangerously - corroding its institutions and practices, while expanding neo-totalitarian governance discourses and practices to the global level. The autocratic corrosion of international human rights law institutions is exacerbated by attempts to weaken accountability under international human rights law from within liberal democracies, amounting to synergic corrosive effects. Yet, the corrosion of practices norms and institutions must not be equated with the elimination of human rights as powerful ideas underpinning responses to the institutional challenges identified here.
CRIS-Team Scopus Importer:2024-06-26
Keywords: autocracy; China; human rights; international rule of law